Integrating Tawhidi values into science and engineering education: a case study - A. Mohamad Al-Batt’hi, Souad; Ahmad , Zuraida (2011)
This article reviews the recent work on integrating Twhidic values by corporating and linking between Quranic and scientific concepts in the texts of some science and engineering subjects and particularly physics for foundation studies. In an attempt to develop the educational process and to enhance and inculcate the value of Tawhid in the students all over the world the author shows how, where and when these values must be inserted within the text of each selected topic. Authors focus on some theories and scientific concepts that explicitly exist in the Holly Quran and explain the relation between them as well as how the science conforming and integrating the Quranic expressions (AYAT) which hence integrating cognition and motivation towards the concept of Tawhid. In this paper Authors suggest new directions for future work of writing up our own text books that integrates scientific, engineering and Islamic concepts. By placing more emphasis on the affective teaching process, this work can become a valuable method toward increased understanding and enjoying the scientific and Islamic concepts.